HANIFAH ANISA FARIZ, - admin, Keguru (KEGURU "Jurnal Ilmu Pendidikan Dasar", 2019)
AbstractThis research aims to develop learning media in the form of monopoly games as disaster preparedness learning for students. The media is MEMO SINCAN (Media Monopoli Siaga Ancaman Bencana). The step in this research are research and data collection, planning, product draft development, initial field testing, field trials, field implementation tests, and final product improvements. Based on the validity analysis and practicality of the media, this media is categorized as very feasible and practical with a validity percentage of 97.5% and practicality percentage of 94.35%.